Concept of the baroque in Travesía de extramares (1950) - Mostacero Castillo, Jonathan Ramiro (2021)
The purpose of this research is to study the concept of the baroque as a fundamental aspect in the vision of the existence of the poetry book Travesía de extramares by Martín Adán (1950). To inquire about the baroque influence on the poet's work, the texts Los exilios interiores by Lauer (1983) and César Vallejo, Martín Adán, Emilio Adolfo Westphalen by Bendezú (2006). The first one will observe the baroque aspect related to hermeticism; of the second, the  examination of the respective poems. On the other hand, the notion of the baroque in  D'Ors will be investigated, where the aforementioned term is exhibited in the manner of a supratemporal category in constant as opposed to the classic. The consequences of our research manage to contemplate the vision of the baroque as an oppositional concept, rather than a strict literary style.